Multi-LoRa - Rede de Comunicação com LoRa multi-rádio e multi-hop para IoT em larga escala - Albuquerque, Eliel de (Universidade do Vale do Rio dos Sinos, 2022)
IoT (Internet of Things) devices must cover large areas of arable land to collect vital information, avoiding financial losses to improve efficiency in agriculture. It is critical to perform data collection on farms where network connectivity is a limitation. LoRaWAN (Long Range Wide Area Network) provides a wide coverage area for IoT applications using unlicensed frequency bands with low power consumption and low throughput. However, LoRaWAN is not suitable for data acquisition on farms with thousands of hectares and coverage equal to or greater than dimensions presented in the literature in regions with slope or slope of soil, a multi-hop LoRa (Long-Range) network has emerged as a promising solution in applications that require deployment with extensions equal to or greater than the area recommended. However, a multihop architecture must be designed to deal with the limitations of deploying LoRa in large-scale scenarios such as its half-duplex nature. This work presents a multi-radio and multi-hop LoRa communication architecture to improve the coverage and service for large-scale IoT deployment in rural areas called Multi-LoRa. Furthermore, we present a hardware prototype to physically implement the Multi-LoRa architecture. The results show that Multi-LoRa effectively mitigates the difficulties of multi-hop communication over LoRa for large-scale IoT deployment. Multi-LoRa reduced delay by 60% and packet loss by 2.9% compared to different Multi-LoRa configurations in a small-scale physical test environment and large-scale emulation environment.
Keywords: LoRa; Multi-rádio; Multi-hop; IoT; Multi-radio; ACCNPQ::Ciências Exatas e da Terra::Ciência da Computação